P841 Barriers to HPV vaccination among gay, bisexual, and other men who have sex with men (gbMSM) in canada: a CIRN study. (14th July 2019) - Grewal, Ramandip; Yeung, Anna; Brisson, Marc; Grennan, Troy; Pokomandy, Alexandra De; Cox, Joseph; Lambert, Gilles; Moore, David; Coutlée, François; Deeks, Shelley; Gardner, Sandra; Griffiths, Dane; et al.
Abstract : Background: Internationally, Canada was one of the first countries to offer free HPV vaccination to young gbMSM. The provinces of British Columbia (BC), Ontario (ON) and Quebec (QC) implemented HPV vaccination programs in 2015–2016 for gbMSM aged 9–26. We explored HPV vaccine initiation and among unvaccinated men, potential barriers to uptake. Methods: Engage is a sexual health study among gbMSM aged 16+ in Vancouver BC, Toronto ON, and Montreal QC, the largest urban centres in each province. Men are recruited via respondent driven sampling (RDS). We estimated the proportion that had initiated HPV vaccination and among unvaccinated men, compared proportions to responses on HPV vaccine knowledge and willingness, healthcare access and sexual orientation disclosure by age (eligible for free vaccination: ≤26 and ineligible for free vaccination: ≥26 years old). Proportions were RDS unadjusted. Results: From 01/2017 to 31/12/2018, 2099 men enrolled (542 Vancouver, 378 Toronto, 1179 Montreal). Their median age was 33 years (IQR 27–46). In Vancouver, Toronto, and Montreal, 48.6%, 44.1% and 44.2% of men aged ≤26 and 24.9%, 30.3% and 7.1% of men aged ≥26 had 1+ dose of the HPV vaccine, respectively. Among unvaccinated men, more men aged ≥26 versus ≤26 accessed healthcare (family doctor/sexual health/HIV care) (87.2% vs 78.9%, p=0.0008) and disclosed their sexual orientation to their family doctor (86.2% vs 64.4%, p<0.0001). A similar proportion of unvaccinated men from each age group had heard of the HPV vaccine (≥26=67.5% vs ≤26=69.0%, p<0.0529). Among unvaccinated men aware of the HPV vaccine, more men aged ≥26 versus ≤26 were willingness to get vaccinated if the vaccine were free and required disclosure of same-sex activity (80.3% vs 61.5%, p=0.0259). Conclusion: Preliminary analyses indicate that HPV vaccine initiation in this population remains suboptimal. Among unvaccinated gbMSM ≤26, accessing healthcare, not disclosing sexual orientation and willingness to get vaccinated may be barriers to vaccine uptake. Disclosure: No significant relationships.